X-Ray Fluorescence, Strength Testing and 3D-Analysis of Steel Fibre Reinforced Concrete Specimen - Mohamad Haslan, Nur Hadirah; Alisibramulisi, Anizahyati; Muhd Sidek, Muhd Norhasri; Hassan, Rohana; Saari, Nadiah; Mohamed Ibrahim, Mohd Johan (Journal of Advanced Industrial Technology and Application, 2022)
This study was focused on steel fiber reinforced concrete (SFRC) specimens subjected to X-Ray Fluorescence (XRF), flexural strength testing, Compressive Strength Test and Rebound Hammer Test method. The experimental result of compression strength was analyzed by 3D Analysis using Stat-Ease Design-Expert V13 to correlate the compressive strengths and compare it to the elemental composition of the concrete structure. The result showed that the amount of Calcium Oxide (CaO) in the sample was lower than the composition of Ordinary Portland Cement (OPC) used. Decreasing of calcium oxide for increase proportion of steel fibre samples show the reaction of cement behaviour into concrete properties mixed with other material properties. Thirty-six (36) beam samples 100mm x 100mm x 500mm and twelve (12) cube samples of 100mm x 100mm x 100m were prepared with a different portions of steel fibre and RC structure as control samples. The percentages of steel fiber used were 0.5%, 1.0% and 1.5% to determine the optimum dosage. All samples were cured for 7, 14 and 28 days. It can be concluded that the analysis shows a low significant effect at an early aged concrete but showing a slightly increased in compression and flexural strength at later age.